2016
DOI: 10.1111/jasp.12413
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐group friendships and outgroup attitudes among Turkish–Kurdish ethnic groups: does perceived interethnic conflict moderate the friendship‐attitude link?

Abstract: We investigated associations between cross‐group friendships, perceived interethnic conflict, and outgroup attitudes in the context of intractable Turkish–Kurdish conflict in Turkey. Measures of cross‐group friendship quantity, perceived conflict, outgroup attitudes, multiculturalism, and outgroup responsibility for conflict were completed by Turkish (N = 320) and Kurdish (N = 153) participants (Mage = 21, 156 males, 317 females). Both cross‐group friendships and perceived conflict were related to outcome vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
50
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(53 citation statements)
references
References 76 publications
2
50
1
Order By: Relevance
“…Previous research has also shown that contact effects may not be always as positive as expected especially among ethnic minorities in a high conflict area (Bagci & Çelebi, 2017a). In line with this finding, Stathi and Crisp (2008) found that the imagined contact strategy failed to lead to higher projection of positive trait to the outgroup among the minority group.…”
Section: Discussionsupporting
confidence: 75%
See 4 more Smart Citations
“…Previous research has also shown that contact effects may not be always as positive as expected especially among ethnic minorities in a high conflict area (Bagci & Çelebi, 2017a). In line with this finding, Stathi and Crisp (2008) found that the imagined contact strategy failed to lead to higher projection of positive trait to the outgroup among the minority group.…”
Section: Discussionsupporting
confidence: 75%
“…Previous research has suggested that imagined contact may be a useful tool to improve intergroup attitudes in settings where direct contact is less likely to occur (Husnu & Crisp, 2010a). Especially, in the Turkish-Kurdish setting where both minority and majority group members perceive a high level of intergroup conflict (Bagci & Çelebi, 2017a), imagining a positive intergroup encounter may work as a first step of a more direct contact intervention (Crisp & Turner, 2009). In fact, it is now known that previous positive contact experiences may protect group members from the detrimental effects of present negative contact experiences in high conflict settings (Paolini, Harwood, Rubin, Husnu, Joyce, & Hewstone, 2014).…”
Section: Gen E Ra L Discussionmentioning
confidence: 99%
See 3 more Smart Citations